First Line Androgen Deprivation Therapy Duration Is Associated with the Efficacy of Abiraterone Acetate Treated Metastatic Castration-Resistant Prostate Cancer after Docetaxel - Li, Jian-Ri; Wang, Shian-Shiang; Yang, Cheng-Kuang; Chen, Chuan-Su; Ho, Hao-Chung; Chiu, Kun-Yuan; Hung, Chi-Feng; Cheng, Chen-Li; Yang, Chi-Rei; Chen, Cheng-Che; Wang, Shu-Chi; Lin, Chia-Yen; et al. (Frontiers in Pharmacology, 2017)
Introduction We performed a chart review study in our castration-resistant prostate cancer (CRPC) patients who received Abiraterone acetate (AA) treatment after docetaxel and identified clinical markers which can predict treatment outcome. Materials and Methods. From 2012 to 2016, 64 patients who received docetaxel after CRPC followed by AA treatment were included. Clinical parameters were recorded and analysis was performed to identify associations between pre-treatment variables and treatment outcome. Results Thirty three patients (51.6%) achieved a decrease in PSA of 50%. The median PSA progression-free survival and overall survival in the total cohort of 64 patients were 6.6 and 24 months, respectively. Adverse events in all grades developed in 35.9% (23/64) patients and mostly were grade 1 or 2. The most common adverse events were gastric upset, hypokalemia and elevated liver function tests. Of the eight variables analyzed, first line androgen deprivation therapy (ADT) duration showed positive association to progression free survival (HR 0.98, 95% CI 0.96-0.99, p=0.012) and overall survival (HR 0.97, 95% CI 0.94-0.99, p= 0.019). Pre-AA PSA and PSA progression ratio showed negative association only to progression free survival (HR 1.0, 95% CI 1.000-1.002, p=0.025, HR 1.01, 95% CI 1.00-1.01, p<0.001 respectively). Conclusions First line ADT duration was positively associated with AA treatment efficacy in progression free survival and overall survival. It can be used as a pre-treatment predictor.